The Impact of the Arms Race on the Economic Growth of the United States and Russia - Sambas, Maimunah; Saputro, Guntur Eko; Hermanto, Djamarel; Rizqiah, Khairul (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The arms race between the United States and the Soviet Union (Russia) during the Cold War had a significant impact on the economic growth of both superpowers. This study examines how the allocation of vast resources for military purposes and threats affected other sectors of the economy. By analyzing historical data on military spending, industrial production, investment, and GDP. The research found that the arms race puts huge pressure on the state budget and creates a trade-off between military spending and investment in productive sectors, which ultimately hampers long-term economic growth in both countries. This study uses secondary data such as journal books, reports from Publish or Perish, Google Scholar, related and relevant websites regarding the arms race and its impact on economic growth through the library research method. The data collection technique used is data triangulation. The purpose of this research is to analyze the impact of the arms race between the US and Russia on the economic growth of both countries. Therefore, it is expected to provide insight and reference for the government in formulating policies regarding the arms race carried out by other countries. The results of this study found the negative impact of the arms race and the importance of placing resources wisely for sustainable economic growth. The impact of the United States and Russia's arms race can hamper long-term economic growth and welfare levels in both countries. Therefore, diplomacy of international cooperation and de-escalation of tensions are necessary to avoid an arms race due to uncontrolled increase in military spending